Intergenerational persistence in income and social class: The impact of within-group inequality - Jo Blanden; Paul Gregg; Lindsey Macmillan (Institute for the Study of Labor (IZA), 2011)
Family income is found to be more closely related to sons' earnings for a cohort born in 1970 compared to one born in 1958. This result is in stark contrast to the finding on the basis of social class; intergenerational mobility for this outcome is found to be unchanged. Our aim here is to explore the reason for this divergence. We derive a formal framework which relates mobility in measured family income/earnings to mobility in social class. Building on this framework we then test a number of alternative hypotheses to explain the difference between the trends, finding evidence of an increase in the intergenerational persistence of the permanent component of income that is unrelated to social class. We reject the hypothesis that the observed decline in income mobility is a consequence of the poor measurement of permanent family income in the 1958 cohort.
urn:nbn:de:101:1-201201107517
Keywords: J13; J31; Z13; 330; intergenerational income mobility; social class fluidity; income inequality; Soziale Mobilität; Soziale Schicht; Einkommen; Intergenerational Mobility; Großbritannien